Pengaruh Digital Marketing, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Pakaian Thrift Toko Kondang Sukoharjo - Moch Nizar Maulana; Sumaryanto (Teewan Journal Solutions, 2026)
This study aims to analyse the influence of digital marketing, price, and product quality on consumer purchasing decisions at Toko Kondang Sukoharjo, a reputable second-hand clothing store (thrift shop) in the Sukoharjo area. The research question is based on the need to understand the determining factors that shape purchasing decisions at this store, with the initial hypothesis that the three independent variables have a significant influence. This study is expected to provide an informative basis for consumers in their decision-making. The method used is a quantitative survey with primary data collected through questionnaires distributed to 101 respondents. The sampling technique used purposive sampling with specific criteria. The results of the data analysis show that partially (t-test), the variables of digital marketing, price, and product quality each have a statistically significant influence on purchasing decisions. Similarly, the results of the simultaneous test (F-test) confirm that these three variables together have a significant effect. The analysis of the coefficient of determination (Adjusted R2) produced a value of 0.741, indicating that 74.1% of the variation in purchasing decisions can be explained by the variables of digital marketing, price, and product quality.